The blood picture of the woman in labor - Picón Reátegui, Emilio (1949)
There have been several hematological studies in 12 women in labor and the results seem to justify the following conclusions: 1.-The 50 percent of women studied had a moderate anemia. 2.-In the group presenting anemia, it could be classified as follows: 33.3 percent of small cell type; Normocytic 50 percent and 16.7 percent hypochromic microcytic erab. 3. Could not find relationship between the frequency of anemia and certain pathophysiological conditions such as age, number of pregnancies and origins of diseased, it is likely that more in relation to dietary habits prior to delivery. 4.-The amount of blood bilirubin and platelet counts were within normal limits. 5.- 66.7 percent of our patients in labor had a sedimentation rate above 15 mm per hour. The sedimentation rate kept a direct relationship with the content of plasma globulins. 6. Leukocytosis was present in 66.7 percent of women in labor. This leukocytosis was conditioned by an increase in relative and absolute polymorphonuclear neutrophils.